The Influence of COVID-19 News for Religious Activities in Lampung using Apriori Algorithm - Nadya Amalia Nasution; Fiqih Satria (Institut Bakti Nusantara, 2021)
The COVID-19 outbreak in 2020, which affected countries in the world, has become a phenomenon that has shaken social life, especially customs in Indonesia. The information about COVID-19 that people get from various sources, such as mass media, social media or word of mouth. Social distancing and calls for “just at home” are being increasingly informed by the government, along with the increase in COVID-19 sufferers in Indonesia, especially in the province of Lampung. Religious activities, especially Islam, which are full of togetherness, such as congregational prayers in mosques, and recitation are among the things that must be undone, along with the government's call to “worship from home” in order to stop the spread of COVID-19. This study seeks to reveal the relationship between information sources, understanding, and people's attitudes towards religious activities, with data mining techniques. That way, we can conclude which media are the most effective in conveying information. The data mining referred to in this study uses a priori algorithm. The priori algorithm is one of the classic data mining algorithms. A priori algorithms are used so that computers can learn association rules, looking for patterns of relationships between one or more items in a dataset. This research was conducted with survey data which were distributed in various districts and cities in the province of Lampung. The results of this study are that there is a connection, if people are afraid of the Covid-19 outbreak and get Covid-19 information through Instagram, they will be relatively obedient, and worship at home. These results can be used by the government in choosing the most appropriate channels/channels, to maximize the dissemination of information, namely through Instagram, especially for millennials.